ANALYSIS OF THE USE OF GUIDED NOTE-TAKING METHODS IN INCREASING THE RESULTS OF SKI LEARNING IN CLASS X MAS SABILAL AKHYAR KUALA BEGUMIT LANGKAT REGENCY - Utami, Rahmi; Yetty, Milfa (Proceeding International Seminar of Islamic Studies, 2023)
This research aims to find out several things regarding the implementation of the guided note-taking method to improve SKI learning outcomes in class X MAS Sabilal Akhyar, the use of the guided note-taking method to improve learning outcomes and improving student learning outcomes in the SKI subject in class X MAS Sabilal Akhyar Kwala Begumit Kec. Binjai Kab. Langkat. Theoretically, this research is expected to obtain a general repertoire of knowledge, especially for writers in the fields of education related to learning methods for improving SKI learning outcomes. This study uses a qualitative research method, which is carried out by taking the steps of collecting information, data collection, classification and analysis of data, and interpretation before making conclusions and reports. It is done with the primary objective of making an accurate description of a situation. The qualitative approach uses "natural characteristics" (natural setting) as a direct, descriptive data source. In this case, the process is more important than the result. The qualitative research analysis tends to be carried out in an inductive manner, and meaning is essential in this study. The results of this study indicate that the guided note-taking method is a learning method that is effective and efficient enough to be applied to the types of SKI lessons that contain lots of explanations and explanations of each material concept explained by the teacher in class.